2017
DOI: 10.15640/jfbm.v5n1a7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Green Banking Practices on Bank�s Environmental Performance: Evidence from Sri Lanka

Abstract: Today, all the sectors of world economy are facing huge challenges to deal with the environmental problems and their related impacts in their day to day businesses. In Sri Lanka, banks are launching green banking initiatives in recent years. Apparently, there are lacunas in empirical studies undertaken in Sri Lankan context regarding green banking and bank's environmental performance. Hence, the objective of this paper is to measure the impact of green banking practices on bank's environmental performance. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 16 publications
5
52
2
3
Order By: Relevance
“…Stakeholders are concerned about business activities that have adverse impacts on society and the environment [2]. As a result, paying greater attention to the environmental issues across the globe has exerted pressure on all industries to become greener, including the financial services and more particularly banks [3][4][5]. As a consequence, the global banking industry has shifted towards an environmentally focused strategy through the adoption of green banking [6].…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholders are concerned about business activities that have adverse impacts on society and the environment [2]. As a result, paying greater attention to the environmental issues across the globe has exerted pressure on all industries to become greener, including the financial services and more particularly banks [3][4][5]. As a consequence, the global banking industry has shifted towards an environmentally focused strategy through the adoption of green banking [6].…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, shifting of societal concern towards environmentally ~ 45 J ournal of Business and Social Sciences (JBSS) friendly practices has been the prime concern of governments, policy makers, business firms and the public justified through a number of dialogues on issues pertaining to environmental protection and `climate change. Couples of years back, issues pertaining to environment were barely relevant to financial sectors (Shaumya & Anton Arulrajah, 2017). However, at the current times banks have been viewed as contributing to pollution through their operations and increasing emission of carbon dioxide via use of airconditions, lights, electronic and fuel equipment, financing environment polluting projects.…”
Section: Introductionmentioning
confidence: 99%
“…This literature review attempts to identify the gap in this study and improves this difference for the development of research. Shaumya and Arulrajah (2017) found that the green banking practices have the positive impact on bank's environmental performance.…”
Section: Literature Reviewmentioning
confidence: 99%